Recalibrating Philippine Criminal Justice: A Legal Analysis of Restorative Justice within the Framework of the Juvenile Justice and Barangay Systems - Theresa Liquigan Eustaquio (Mimbar Keadilan, 2026)
The Philippine criminal justice system remains predominantly retributive, shaped by colonial legacies and a legal culture deeply entrenched in punitive responses to crime. While recent legislation, particularly the Juvenile Justice and Welfare Act (RA 9344), has introduced restorative justice mechanisms, their implementation remains limited in scope, uneven across jurisdictions, and largely confined to youth offenders. This creates a normative inconsistency that undermines the constitutional aspirations for a humane, equitable, and socially responsive justice system. This paper critically examines the structural contradictions within the current legal framework and assesses the potential of restorative justice as a legal and moral alternative in the Philippine context. Employing a doctrinal legal research method, supported by socio-legal analysis, the study investigates statutory enactments, jurisprudential developments, and institutional practices to map the operational boundaries and normative gaps in restorative justice implementation. The findings reveal that restorative justice in the Philippines lacks a coherent statutory foundation beyond juvenile justice, suffers from institutional fragmentation, and is hindered by the absence of inter-agency coordination among the DOJ, DSWD, LGUs, and civil society stakeholders. Despite this, the study affirms that restorative justice aligns with constitutional mandates on due process, social justice, and human dignity. It also offers a culturally resonant approach to justice, particularly when integrated with indigenous and community-based mechanisms. This paper concludes with a call for statutory reform, institutional redesign, and pedagogical transformation to mainstream restorative justice as a constitutionally grounded alternative to the prevailing punitive model.